Pembuatan Aplikasi Toko Komputer dengan CRUD Berbasis Visual Basic dan MySQL - Riadi, Rafi Putra Bagus; Tedja, Briant; Basatha, Risky (Al-DYAS, 2025)
This study aims to develop a desktop-based computer store application called "Onestop Komputer" using Visual Basic and MySQL by implementing CRUD (Create, Read, Update, Delete) functions to support effective store data management. This application is designed to overcome the constraints of manual data management that is time-consuming and prone to errors, especially in recording transactions and inventory. The research method includes the needs analysis stage, system design using the Entity-Relationship Diagram (ERD) model, application coding with Visual Studio using the Visual Basic language, and integration with the MySQL database. The data was tested using a functionality test to ensure that the CRUD feature runs as expected. The results of the study show that this application is able to facilitate the management of goods, customers, and sales and purchase transaction data with a simple and easy-to-use interface. In conclusion, the "Onestop Komputer" application has succeeded in becoming an efficient solution in supporting computer store operations, especially in digital data management.